Free to Die: A Lutheran-Relational Approach to Medical Assistance in Dying - Kayko Driedger Hesslein (Religions, 2020)
In 2016, Canada legalized Bill C-14, which removed from the Criminal Code medical assistance in dying (MAID) under certain circumstances. In essence, the Bill legalized what is commonly described as euthanasia, under the provisions that the patient has a terminal medical diagnosis, anticipates extreme suffering, is at least 18 years old and still maintains their own medical power of attorney, has received the same diagnosis from two separate doctors, and requests such a procedure without duress. The bill exempts doctors and nurses from culpability in murder, along with those aiding the medical staff. The bill replaces sections of the Criminal Code that criminalize death by suicide. In this article, I first review the theological and historical interpretation of suicide within the Christian church. I then offer a specifically Lutheran feminist framework of our baptism into death, Luther’s explanation of the First Commandment, and Christian freedom to affirm Christians’ faithful decisions in seeking medical assistance in dying.